Study design and methods for a randomized crossover trial substituting brown rice for white rice on diabetes risk factors in India. (3rd October 2015) - Wedick, Nicole M.; Sudha, Vasudevan; Spiegelman, Donna; Bai, Mookambika Ramya; Malik, Vasanti S.; Venkatachalam, Siva Sankari; Parthasarathy, Vijayalaksmi; Vaidya, Ruchi; Nagarajan, Lakshmipriya; Arumugam, Kokila; Jones, Clara; Campos, Hannia; et al.
Abstract: India has the second largest number of people with diabetes in the world following China. Evidence indicates that consumption of whole grains can reduce the risk of type 2 diabetes. This article describes the study design and methods of a trial in progress evaluating the effects of substituting whole grain brown rice for polished (refined) white rice on biomarkers of diabetes risk (glucose metabolism, dyslipidemia, inflammation). This is a randomized controlled clinical trial with a crossover design conducted in Chennai, India among overweight but otherwise healthy volunteers aged 25–65 y with a body mass index ≥23 kg/m 2 and habitual rice consumption ≥200 g/day. The feasibility and cultural appropriateness of this type of intervention in the local environment will also be examined. If the intervention is efficacious, the findings can be incorporated into national-level policies which could include the provision of brown rice as an option or replacement for white rice in government institutions and food programs. This relatively simple dietary intervention has the potential to substantially diminish the burden of diabetes in Asia and elsewhere.